Media literacy, information literacy, and novice voters combating online political misinformation - Kurniasih, Erni; Damayani, Ninis Agustini; Zubair, Feliza (Jurnal Kajian Informasi dan Perpustakaan, 2024)
Novice voters are susceptible to political misinformation, which can influence democratic decision-making. Thus, reducing the negative impact of political misinformation is essential to support more democratic elections. Utilizing the Stimulus-Organism-Response theoretical framework, this research examines four hypotheses concerning the correlation of media literacy and information literacy on the capability of novice voters to recognize misinformation about politics and their intention to disseminate it on social networks. A quantitative research approach employing cross-sectional surveys was utilized. The sample consisted of 380 novice voters comprising high school students in Cianjur Regency, selected through a stratified random sampling method. Data were collected through online surveys using Google Forms and tested using the application of the Statistical Package for the Social Sciences. According to the findings, media literacy and information literacy simultaneously significantly impact novice voters' competence to recognize political misinformation on social network sites, and higher media and information literacy scales correlate with lower intentions to disseminate political misinformation on social platforms. The findings conclude that media literacy and information literacy perform a crucial function in determining the behavior of beginner voters regarding political misinformation on social media. These findings also support policymakers, media organizations, and educational institutions in designing more effective literacy programs.